Perceived psychological reactions to second wave of pandemic COVID-19 Among Working Adult Indonesians: An online survey study - Edi Sampurno Ridwan; Sofyan Indrayana; Asep Badrujamaludin; Dedi Supriadi; Nuh Huda; Priyanto Priyanto; Qori Ila Saidah; Aan Sutandi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: The Corona Virus Disease (Covid-19) pandemic caused serious health consequences including mental health issues. Thus, gaining insight into the emergence of mental health problems including fear, anxiety and stress in society during the second wave Covid-19 pandemic is imperative.  Objectives: This study aimed to identify the psychological reactions of working Indonesians living in five metropolitan cities in Java Island and its association with personal characteristics during the second wave Covid-19 pandemic.Methods: This cross-sectional study included a total of 916 respondents from five metropolitan cities in the Island of Java that was voluntarily completing the anonymous online survey. The data were administered by using the Indonesian version of Perceived Stress Scale (PSS), Covid-19 Anxiety Scale (CAS), and Fear of Covid-19 Scale (FCS). Bivariate and multivariate analysis were performed using non-parametric methods due to non-normal distribution data. Significance for hypothesis testing was set with p-value 0.05 on 95% Confidence Interval. Data was analyzed using software STATA14 of StataCorp.Results: A total of 916 respondents were included, with the median of age being 28 years old. Perceived fear and anxiety to Covid-19 among working individuals was low (35.92% and 40.94%), yet they were on moderate and high-levels of stress (31.88% and 45.52%) respectively. After adjusted all predictors, age was a significant predictor to the level of fear (p< 0.001), anxiety (p= 0.05), and stress (p< 0.001). The first dose of vaccination significantly predicted a reduction in the fear of Covid-19 (p= 0.045).Conclusions: Increasing a year of age predicted the reduction of fear, anxiety, and perceived of stress to Covid-19. First dose vaccination significantly reduced the fear to Covid-19.